Colchicine plus Dapsone in Colchicine‐Resistant FMF Patients - Farhad Salehzadeh; A. Enteshary; M. Moshkbar (Case Reports in Rheumatology)
Five to ten percent of FMF patients have unfavorable response to the colchicine as a standard therapy. Biologic treatments have been shown to be highly effective, but there are often unavailable, because the price is unaffordably high. This study shows the striking effect of combined dapsone and colchicine therapy in such patients and recommends it as an alternative therapy in colchicine-resistant (CR) patients.